Analisis Faktor Kualitas Pelayanan di Bank Syariah (Studi Pada PT Bank Muamalat Indonesia) - S. Suryani (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2014)
Factor Analysis on Services Quality in Islamic Bank (Study at PT Bank Muamalat Indonesia). The aim of this study is to determine and identify the factors forming quality of service in PT. Bank Muamalat Indonesia, Tbk Branch Medan. Instruments of research use questionnaires and factor analysis. This research is quantitative research using survey methods. The sample method that used in this research is accidental sampling. The reliability and validity test shown that 13 question had been fulfilled the reliability and validity requirements. From the extraction gives three factors. Factor 1 explained 45,299%, factor 2 explained 12,819%, and factor 3 explained 8,904%. The results show that quality of communication is dominant factor to explain service quality. Then product innovation and physical aspects DOI:10.15408/aiq.v6i2.1233